Ni en haut, ni en bas : la sélection dans la formation d’assistant.e de service social - Ruggero Iori (Cahiers de la Recherche sur l'Education et les Savoirs)
In this article, we examine the selection process in social work training. During these evaluations, vocational schools attempt to assess the “personality” of the candidates, who are predominantly women. By questioning the dynamics of selection for this post-baccalaureate professional curriculum while moving away from the professional rhetoric, this article looks at what is behind the quest of this “personality”. We will see how these committees try to identify educational, social and gendered characteristics - not very explicit as prerequisites - centered on the hexis of the applicants, thus leading to the permanence of educational, social and gender hierarchies upon entry into an intermediary profession in the public sector.